A proinflammatory role for IL-18 in rheumatoid arthritis - Gracie, J. Alastair (American Society for Clinical Investigation, 1999)
IL-18 is a novel cytokine with pleiotropic activities critical to the development of T-helper 1 (Th1) responses. We detected IL-18 mRNA and protein within rheumatoid arthritis (RA) synovial tissues in significantly higher levels than in osteoarthritis controls. Similarly, IL-18 receptor expression was detected on synovial lymphocytes and macrophages. Together with IL-12 or IL-15, IL-18 induced significant IFN-γ production by synovial tissues in vitro. IL-18 independently promoted GM-CSF and nitric oxide production, and it induced significant TNF-α synthesis by CD14(+) macrophages in synovial cultures; the latter effect was potentiated by IL-12 or IL-15. TNF-α and IFN-γ synthesis was suppressed by IL-10 and TGF-β. IL-18 production in primary synovial cultures and purified synovial fibroblasts was, in turn, upregulated by TNF-α and IL-1β, suggesting that monokine expression can feed back to promote Th1 cell development in synovial membrane. Finally, IL-18 administration to collagen/incomplete Freund’s adjuvant–immunized DBA/1 mice facilitated the development of an erosive, inflammatory arthritis, suggesting that IL-18 can be proinflammatory in vivo. Together, these data indicate that synergistic combinations of IL-18, IL-12, and IL-15 may be of importance in sustaining both Th1 responses and monokine production in RA. J. Clin. Invest. 104:1393–1401 (1999).